Sponsorship-based health care programs and their impact on employees' motivation for physical activity. Issue 2 (15th March 2021) - Bjerke, Rune; Elvekrok, Ingunn
ABSTRACT: Research question: This study investigates the impact of a healthcare portal and employee attitude toward a healthcare program on sponsorship-based employee motivation to do physical exercises. Research methods: Applying a case methodology, the sponsorship object was the Norwegian National Cross-Country Skiing Team, and the sponsor was Aker, a major international corporation involved in fishing, offshore construction and engineering. By means of mixed methods, qualitative data were collected from 10 employees and then, quantitative data from 544 employees were used to test the hypotheses. Results and Findings: The findings show that the user-friendliness of the healthcare portal, and the attitude towards the health care program are significant predictors of employees' sponsorship-based motivation to do physical exercises. These findings held when controlling for sex, education, income, portal usage, and physical activity level. Implications: These findings have practical implications for sponsors and the use of sponsorships as a strategic tool to improve employee matters. 'The Internal CSR and Sponsorship-linked Health Care Strategy Model' is presented. This paper establishes connections between internal sponsorship activation, employee health care program, and their motivation to do physical exercise.